2016
DOI: 10.1073/pnas.1603817113
|View full text |Cite
|
Sign up to set email alerts
|

Complete in vitro generation of fertile oocytes from mouse primordial germ cells

Abstract: Reconstituting gametogenesis in vitro is a key goal for reproductive biology and regenerative medicine. Successful in vitro reconstitution of primordial germ cells and spermatogenesis has recently had a significant effect in the field. However, recapitulation of oogenesis in vitro remains unachieved. Here we demonstrate the first reconstitution, to our knowledge, of the entire process of mammalian oogenesis in vitro from primordial germ cells, using an estrogenreceptor antagonist that promotes normal follicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(157 citation statements)
references
References 42 publications
3
145
0
1
Order By: Relevance
“…Following improvements in the technique and after alterations to the culture medium several mouse embryos and offspring have been obtained using oocytes that have been IVG then combined with IVM and IVF (O'Brien et al, 2003). More recently, in vitro systems that support the complete development of mouse oocytes starting from induced pluripotent stem cells (Hikabe et al, 2016) and from primordial germ cells (Morohaku et al, 2016) have been reported and these systems have resulted in competent oocytes that produce embryos and live young.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following improvements in the technique and after alterations to the culture medium several mouse embryos and offspring have been obtained using oocytes that have been IVG then combined with IVM and IVF (O'Brien et al, 2003). More recently, in vitro systems that support the complete development of mouse oocytes starting from induced pluripotent stem cells (Hikabe et al, 2016) and from primordial germ cells (Morohaku et al, 2016) have been reported and these systems have resulted in competent oocytes that produce embryos and live young.…”
Section: Discussionmentioning
confidence: 99%
“…The most immature stage of follicles (primordial) can be grown in a two-step culture system to produce oocytes that can be fertilized, and live offspring have been produced from these in vitro grown (IVG) oocytes (Eppig and O'Brien, 1996;O'Brien et al, 2003). Recent reports have shown that the process of mouse oocyte development can be recapitulated in vitro starting from primordial germ cells and induced pluripotent stem cells (Hikabe et al, 2016;Morohaku et al, 2016) but little is known about the potential for human IVG oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the system produced MII oocytes, followed by fertilized eggs, from mitotic PGCs in the fetal ovaries, thereby for the first time demonstrating the successful completion of meiosis in a female germ line in culture (Fig. 2) (Morohaku et al 2016). Apart from the completion of meiosis, the culture system provides two important components that are requisite to achieving a robust production of oocytes in culture.…”
Section: Reconstitution Of the Female Germ Line: Oogenesis In Organ Cmentioning
confidence: 94%
“…The GV oocytes were then cultured in a medium containing LH and EGF. Importantly, the resultant MII oocytes from the culture were capable of fertilization and full-term development (Morohaku et al 2016).…”
Section: Proof Onlymentioning
confidence: 99%
“…Recently, we successfully demonstrated the complete in vitro generation of fertile mouse oocytes from PGCs for the first time 63. Such an in vitro system is expected to unravel the mechanisms of oogenesis and preserve female gametes.…”
Section: Introductionmentioning
confidence: 99%